2020
DOI: 10.1007/s10639-020-10168-6
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of mobile applications for teaching-learning process in rural girls’ schools in India: an empirical study

Abstract: The purpose of this study is to identify the factors that can impact the adoption of mobile apps for teaching-learning process focusing on the girls' school in rural India. The hypotheses were proposed and a conceptual model has been developed. There is a survey work conducted to collect the data from different respondents using a convenience sampling method. The model has been validated statistically through PLS-SEM analysis covering feedbacks of 271 effective respondents. The study highlights the impact of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 74 publications
(76 reference statements)
1
23
1
1
Order By: Relevance
“…Thus, co-creation activities can be fruitfully implemented either by spreading the feedbacks of the customers by social media platforms or by PI (Kar and Chatterjee, 2018;Thürmer et al, 2020). At the BOP level, the consumers are not to that extent skillful to use social media platforms such as Facebook and Twitter, especially, for cocreation activities for the aged persons, as at BOP level it is observed that only most of the young people possess smartphones (Lenhart et al, 2015;Majumdar et al, 2019). The social media platforms will help the consumers at the BOP level for ensuring media-rich, real-time and highly personalized social collaboration and interactions between the consumers and the firms helpful for improving cocreation activities (Rishika et al, 2013;Sreenivasulu and Chatterjee, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, co-creation activities can be fruitfully implemented either by spreading the feedbacks of the customers by social media platforms or by PI (Kar and Chatterjee, 2018;Thürmer et al, 2020). At the BOP level, the consumers are not to that extent skillful to use social media platforms such as Facebook and Twitter, especially, for cocreation activities for the aged persons, as at BOP level it is observed that only most of the young people possess smartphones (Lenhart et al, 2015;Majumdar et al, 2019). The social media platforms will help the consumers at the BOP level for ensuring media-rich, real-time and highly personalized social collaboration and interactions between the consumers and the firms helpful for improving cocreation activities (Rishika et al, 2013;Sreenivasulu and Chatterjee, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It is not easy for the consumers at BOP to reach the firms for providing their inputs to co-create values (Lassaga and Lanfranchi, 2012;Kumar et al, 2019aKumar et al, , 2019b. It is observed that young persons at BOP use smartphones and they might connect with the producers toward providing feedbacks for co-creating values (Majumdar et al, 2019) The aged persons of BOP are found using social media platform to a lesser extent which is the normal scenario in the developing economies (Chatterjee, 2020b). Naturally, aged people at the BOP level cannot or very little can connect with the producers of the products or the service providers to provide their experience and feedbacks for cocreating values with the help of social media platforms, as they usually do not use these devices (Kar and Chatterjee, 2020).…”
Section: Age and Social Media Usagementioning
confidence: 99%
“…It is feasible to define a conceptual framework for both learners and teachers for selecting high-quality learning resources. In addition, the adoption of hardware devices including mobile phones [63], wearable devices [64] and so on can be an important factor for further investigation. Future research is therefore advised to be conducted in such directions.…”
Section: Discussionmentioning
confidence: 99%
“…Chatterjee et al ( 2020 ) recommended partial least squares structural equation modelling (PLS-SEM) to discover the factors affecting mobile learning techniques focusing on rural education for females in India. The strategy gave educational leaders and technology managers praiseworthy insights to explore and encourage mobile apps to study and affect economically depressed Indian girls' schools.…”
Section: Literature Review Of Mobile Learning Resource In Smart Educationmentioning
confidence: 99%